Identification and Characterization of Volatile Organic Compounds Based on GC-IMS Technology in Different Organs of Lilium brownii var. viridulum and After Bud-Removal and Non-Bud-Removal Treatments - Xiaoling Li; Zhihui Wang; Chaowen Hou; Xiujuan Gong; Zexiang Liu; Yuhe Shi; Jianye Yan; Qiaozhen Tong (Molecules)
Lilium brownii var. viridulum (Longya lily) is a widely used medicinal and culinary plant in China that is valued for its potential applications and development opportunities. The bulbs of Longya lily contain a variety of active components; volatile oil, as one of the main biologically active compounds, has been widely studied, and the stems, leaves, and flowers of Longya lily are also rich in volatile organic compounds (VOCs) and related pharmacological effects, but the horizontal comparison of different organs of lily plants is lacking. In order to promote the sustainable development of resources, the composition characteristics and differences of bulbs, stems, leaves, and flowers, as well as two crop management methods (bud-removal and non-bud-removal), were comprehensively studied by GC-IMS technology in this study. Additionally, multivariate statistical analyses were used to identify the key components responsible for the observed differences among the plant organs and treatments. The research identified a total of 93 volatile organic compounds in Longya lily samples, primarily consisting of aldehydes, alcohols, ketones, and esters. If the VOCs of Longya lily are to be used as raw materials, it is advisable to choose flowers and leaves with a higher concentration of these components for harvesting. Notably, bulbs that were non-bud-removal exhibited a greater total content of volatile flavor substances compared to those that were treated with bud removal, with hexanal-D and (E)-2-hexenal-D being the most prevalent volatile organic compounds. This study provided theoretical support for the harvesting parts and crop management methods of Longya lily based on volatile organic compounds and promoted the high-quality development of the Longya lily industry.